Eight weeks of intermittent hypoxic training improves submaximal physiological variables in highly trained runners - Holliss, B. A.; Burden, R. J.; Jones, A. M.; Pedlar, C. R. (The Journal of Strength and Conditioning Research, 2014)
It is unclear whether intermittent hypoxic training (IHT) results in improvements in physiological variables associated with endurance running. Twelve highly trained runners (VO2peak 70.0 ± 3.5 ml/kg/min) performed incremental treadmill tests to exhaustion in normobaric normoxia and hypoxia (16.0% FIO2) to assess submaximal and maximal physiological variables and the limit of tolerance (T-Lim). Participants then completed 8 weeks of moderate to heavy intensity normoxic training (control [CONT]) or IHT (twice weekly 40 minutes runs, in combination with habitual training), in a single blinded manner, before repeating the treadmill tests. Submaximal heart rate decreased significantly more after IHT (-5 ± 5 b/min; p = 0.001) than after CONT ( -1 ± 5 b/min; p = 0.021). Changes in submaximal VO2 were significantly different between groups (p </= 0.05); decreasing in the IHT group in hypoxia (-2.6 ± 1.7 ml/kg/min; p = 0.001) and increasing in the CONT group in normoxia (+1.1 ± 2.1 ml/kg/min; p = 0.012). There were no VO2peak changes within either group, and while T-Lim improved post-IHT in hypoxia (p = 0.031), there were no significant differences between groups. Intermittent hypoxic training resulted in a degree of enhanced cardiovascular fitness that was evident during submaximal, but not maximal intensity exercise. These results suggest that moderate to heavy intensity IHT provides a mean of improving the capacity for submaximal exercise and may be useful for pre-acclimatization for subsequent exercise in hypoxia, but additional research is required to establish its efficacy for athletic performance at sea level.